Overlying strata structural modeling and support applicability analysis for large mining-height stopes. (January 2019) - Wen, Zhijie; Xing, Enrui; Shi, Shaoshuai; Jiang, Yujing
Abstract: After examining the roof strata movement pattern of fully mechanized mining (or caving) with large mining height, a roof structural model for large mining-height stopes was established based on their overlying rock structure; the overlying rock structure and movement pattern of these stopes were investigated; a method for determining the support working load and yield under "given deformation" and "limited deformation" states was proposed; the concept of immediate roof in mining operation with large mining height was modified; the roof control design criteria and support load calculation method for large mining-height stopes were established. The result indicates that increases in the mining height will largely increase the thickness of the immediate roof as well as the possibility of hard rock with large-span suspension top in the immediate roof. The key strata of the main roof having notable influences to stope strata behavior can be divided into two types of structures: a "single key stratum" structure and a "double key strata" structure. If the main roof was a "double key strata" structure, it will be important to prevent both threats like roof cutting or prop over yield in response to movement of the underlying key stratum, and the dynamic pressure impact to the stope in times of weighting of the overlying key stratum. Accurately determining the position, thickness and potential maximum suspended span of the suspension top was the key for the roof control design and support selection calculation for large mining-height stopes. Highlights: A method for determining the support working load and yield under two deformation states was proposed. The concept of immediate roof in mining operation with large mining height was modified. The roof control design criteria and support load calculation method for large mining-height stopes were established.